Death is that man taking names : intersections of American medicine, law, and culture - Burt, Robert A., 1939-2015. (Berkeley : University of California Press ; New York : Milbank Memorial Fund, 2002)
The American culture of death changed radically in the 1970s. For terminal illnesses, hidden decisions by physicians were rejected in favor of rational self-control by patients asserting their "right to die"--Initially by refusing medical treatment and more recently by physician-assisted suicide
Pursuing the good death -- Hidden death -- Death at war -- Judges and death -- Doctors and death -- Choosing death -- The death penalty -- All the days of my life.
Includes index.
Notes: p. 187-218.
Print version record.
Includes bibliographical references (pages 187-218) and index.
English.
JSTOR
Keywords: Death; Terminal care -- United States; Death -- Social aspects -- United States; Death; United States; Mort -- Aspect social -- États-Unis.; Soins en phase terminale -- États-Unis.; Mort; deaths; SOCIAL SCIENCE -- Death & Dying; FAMILY & RELATIONSHIPS -- Death, Grief, Bereavement; MEDICAL -- History; Death; Death -- Social aspects; Terminal care; United States